Wage structure effects of international trade: Evidence from a small open economy - Philip Du Caju; François Rycx; Ilan Tojerow (National Bank of Belgium, 2011)
In the last few decades, international trade has expanded not only between industrialised countries, but also between high- and low-wage countries. This important change has raised questions on how international trade affects the labour market. In this spirit, this paper aims to investigate the impact of international trade on wage dispersion in a small open economy. It is one of the few to: i) use detailed matched employer-employee data to compute industry wage premia and disaggregated industry level panel data to examine the impact of changes in exports and imports on changes in wage differentials, ii) analyse the impact of imports according to the country of origin. Looking at the export side, we find a positive effect of exports on the industry wage premium. The findings also show that import penetration from low-income countries has a significant and negative impact on inter-industry wage differentials, while imports from high-income countries seem to have a more ambiguous impact on the wage structure. The results suggest that trade with low-income and high-income countries has different effects on inter-industry wage differentials.
Keywords: F16; J31; 330; wage structure; inter-industry wage differentials; international trade; matched employer-employee data; Lohnstruktur; Branche; Internationale Wirtschaft; Export; Import; Kleine offene Volkswirtschaft; Schätzung; Belgien